GM-CSF: A Double-Edged Sword in Cancer Immunotherapy - Kumar, Anil; Taghi Khani, Adeleh; Sanchez Ortiz, Ashly; Swaminathan, Srividya (Frontiers in Immunology, 2022)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a cytokine that drives the generation of myeloid cell subsets including neutrophils, monocytes, macrophages, and dendritic cells in response to stress, infections, and cancers. By modulating the functions of innate immune cells that serve as a bridge to activate adaptive immune responses, GM-CSF globally impacts host immune surveillance under pathologic conditions. As with other soluble mediators of immunity, too much or too little GM-CSF has been found to promote cancer aggressiveness. While too little GM-CSF prevents the appropriate production of innate immune cells and subsequent activation of adaptive anti-cancer immune responses, too much of GM-CSF can exhaust immune cells and promote cancer growth. The consequences of GM-CSF signaling in cancer progression are a function of the levels of GM-CSF, the cancer type, and the tumor microenvironment. In this review, we first discuss the secretion of GM-CSF, signaling downstream of the GM-CSF receptor, and GM-CSF's role in modulating myeloid cell homeostasis. We then outline GM-CSF's anti-tumorigenic and pro-tumorigenic effects both on the malignant cells and on the non-malignant immune and other cells in the tumor microenvironment. We provide examples of current clinical and preclinical strategies that harness GM-CSF's anti-cancer potential while minimizing its deleterious effects. We describe the challenges in achieving the Goldilocks effect during administration of GM-CSF-based therapies to patients with cancer. Finally, we provide insights into how technologies that map the immune microenvironment spatially and temporally may be leveraged to intelligently harness GM-CSF for treatment of malignancies.